Ketahanan Korosi Sambungan Friction Stir Welding dengan Variasi Material Pin Tool - Istyawan Priyahapsara; Bahrudin Yusuf Habibie (Jurnal Engine: Energi, Manufaktur, dan Material, 2020)
The use of friction stir welding (FSW) for welding materials that have low weldability such as aluminum is a breakthrough in manufacturing. Therefore, FSW is widely used in aircraft structures. FSW has advantages such as superior mechanical properties, green manufacturing, energy saving, and others. Despite its advantages, there have been very few studies analyzing corrosion in FSW. This study aims to find out whether there is corrosion in the FSW connection with the variations of the pin material which serves as a soft metal stirrer in the FSW process. The method of joining the material is carried out by a friction stir welding (FSW) process using the pin tool ST60, ST60 hardened, and stainless-steel with a plate-shaped specimen. After friction stir welding (FSW) connection and temperature measurement on the specimen, then the specimen is cleaned and weighed. After that, corrosion testing was carried out for 14 days (336 hours) using the immersion test method, which was immersed in seawater corrosive media. Calculation of the corrosion rate using the weight loss method. Then take photos of the microstructure to determine the type of corrosion that is formed. The lowest corrosion rate was on the specimen with a stainless-steel pin tool with an average corrosion rate of 0.3254 mpy. The corrosion that is formed on specimens that has been welded is a type of exfoliation corrosion and corrosion causes pits to occur.Penggunaan friction stir welding (FSW) untuk pengelasan material yang memiliki mampu las rendah seperti alumunium merupakan terobosan dalam dunia manufaktur. Oleh karena itu, FSW banyak digunakan dalam struktur pesawat terbang. FSW memiliki keunggulan seperti sifat mekanis yang superior, manufaktur hijau, hemat energi, dan lain lain. Terlepas keunggulannya, hanya terdapat sedikit penelitian yang menganalisis korosi dalam FSW. Penelitian ini bertujuan untuk mencari tahu apakah ada korosi dalam penyambungan FSW dengan variasi material pin yang bertugas sebagai pengaduk logam lunak dalam prosess FSW. Metode penyambungan material dilakukan dengan proses friction stir welding (FSW) menggunakan pin tool ST60, ST60 hardened, dan stainless-steel dengan spesimen berbentuk plat. Setelah dilakukan sambungan friction stir welding (FSW) dan pengukuran temperatur pada spesimen, selanjutnya dilakukan pembersihan spesimen dan penimbangan. Setelah itu dilakukan pengujian korosi selama 14 hari (336 jam) dengan menggunakan metode immersion test yaitu direndam dengan media korosif air laut. Perhitungan laju korosi dengan manggunakan metode weight loss. Kemudian dilakukan pengambilan foto struktur mikro untuk mengetahui jenis korosi yang terbentuk. Nilai laju korosi yang paling rendah yaitu pada spesimen dengan pin tool stainless-steel dengan nilai rata-rata laju korosi 0,3254 mpy. Korosi yang terbentuk pada spesimen yang telah dilakukan pengelasan merupakan jenis exfoliation corrosion dan korosi menyebabkan terjadinya pits.